2016
DOI: 10.13004/kjnt.2016.12.2.148
|View full text |Cite
|
Sign up to set email alerts
|

A Viewpoint on Treatment of Traumatic Bilateral Basal Ganglia Hemorrhage in a Child: Case Report

Abstract: Traumatic basal ganglia hemorrhage (TBGH) is a rare presentation of head injuries. Bilateral lesions are extremely rare. The pathophysiologic mechanism of bilateral TBGH seems to be the same as diffuse axonal injury. However, limited information about childhood bilateral TBGH is available in the literature. We report the case of a child with bilateral TBGH treated with stereotactic aspiration of hemorrhage and periodic urokinase irrigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…3 In a study Moe et al, it was demonstrated that when associated with DAI affecting unilateral and bilateral BG, they represent 18% and 2%, respectively, 11 being extremely rare in the pediatric population. 9 Chung et al, 4 in a study with 309 pediatric TBI patients, showed that all BG lesions were unilateral and represented only 2.5%. Basal ganglia traumatic hematoma is often small, uni or bilateral, located in the internal capsule and lenticular nucleus (putamen and globus pallidus), 2 which may occur in the thalamus and caudate nucleus, 12 and it may be accompanied by cranial fracture, brain stem lesions, subarachnoid hematoma, 3 EDH, and SDH.…”
Section: Discussion Epidemiologymentioning
confidence: 99%
See 2 more Smart Citations
“…3 In a study Moe et al, it was demonstrated that when associated with DAI affecting unilateral and bilateral BG, they represent 18% and 2%, respectively, 11 being extremely rare in the pediatric population. 9 Chung et al, 4 in a study with 309 pediatric TBI patients, showed that all BG lesions were unilateral and represented only 2.5%. Basal ganglia traumatic hematoma is often small, uni or bilateral, located in the internal capsule and lenticular nucleus (putamen and globus pallidus), 2 which may occur in the thalamus and caudate nucleus, 12 and it may be accompanied by cranial fracture, brain stem lesions, subarachnoid hematoma, 3 EDH, and SDH.…”
Section: Discussion Epidemiologymentioning
confidence: 99%
“…The poor prognosis of patients with BGTH 4 is related to the global characteristic of this brain lesion, 13 associated with the presence of intracranial hypertension, 5 presenting a poorer prognosis rate higher than other traumatic intracranial hemorrhage types. 9 The factors associated with poor prognosis are age > 60 years, DAI, large volume hematoma, extra-axial hematomas, abnormal pupillary and motor responses, severe TBI 14,16 and late hematoma increase. 2 Zakharova et al, 19 in a study with 278 patients, demonstrated that lesions located in the BG have a prognosis of adverse outcomes such as vegetative state, severe neurological deficit, and death.…”
Section: Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 1 ] Sudden acceleration or deceleration forces that causes shearing of the lenticulostriate or the anterior choroidal artery will result in BG bleed. [ 2 ] Although rare bilateral BG hematoma following trauma has been reported,[ 3 ] the eloquent nature of this region is responsible for the severity of symptoms even with a small size hematoma. Moreover, the extent of involvement of the pyramidal or extrapyramidal pathway will determine the residual deficit.…”
mentioning
confidence: 99%